Integrating Citizen Engagement in Program Design Egypt's Sustainable Rural Sanitation Services Program Experience - Galeza, Kamila (World Bank, Washington, DC, 2018)
Citizen engagement is not a new concept in the world of development. Notions of social accountability, citizen participation, voice, have been around development programs for many years. Adopted in 2014, The Strategic Framework for Mainstreaming Citizen Engagement in World Bank Group operations was developed to systematically mainstream citizen engagement by including beneficiary feedback in WBG-supported operations. The Strategic Framework defines citizen engagement as a two-way interaction between citizens and governments or the private sector within the scope of WBG interventions. This approach gives citizens a stake in decision-making to improve the intermediate and final development outcomes. Evidence suggests that engaging citizens can improve accessibility, coverage and quality of service delivery. Egypt’s Sustainable Rural Sanitation Services Program for Results – aims to strengthen institutions and policies to increase access to and improve rural sanitation services in the governates of Beheira, Dakahlia and Sharkiya.